2004
DOI: 10.1051/0004-6361:20040418
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic models for βCephei variables

Abstract: Abstract.A hydrodynamical model is generated for the high-amplitude β Cephei star BW Vulpeculae, and the spectral line profiles are calculated for different pulsational phases. The pulsational characteristics and line profiles are compared with recent observational data obtained during seven consecutive nights in August 2000. We found a generally good agreement in the basic photometric and spectral parameters. Two strong shock waves appear during one period, and the "stillstand" is due to the gas dynamics betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 12 publications
3
21
0
1
Order By: Relevance
“…In addition, radiative transfer is considered in the outer layers to produce a realistic atmosphere model. The derived quantities have been found to be in good agreement with observations for different classes of pulsators such as RR Lyrae , RV Tauri (Fokin 2001), post-AGB (Jeannin et al 1997), BL Herculis (Fokin & Gillet 1994) and more recently β Cephei stars (Fokin et al 2004). In particular, this model has already been used in the case of δ Cep (Fokin et al 1996).…”
Section: This Worksupporting
confidence: 76%
“…In addition, radiative transfer is considered in the outer layers to produce a realistic atmosphere model. The derived quantities have been found to be in good agreement with observations for different classes of pulsators such as RR Lyrae , RV Tauri (Fokin 2001), post-AGB (Jeannin et al 1997), BL Herculis (Fokin & Gillet 1994) and more recently β Cephei stars (Fokin et al 2004). In particular, this model has already been used in the case of δ Cep (Fokin et al 1996).…”
Section: This Worksupporting
confidence: 76%
“…Therefore, as already observed in other stars undergoing strong non linear motions (see e.g. Fokin et al 2004), irregularities are present in the shock intensity, due to an atmospheric time relaxation that is longer than the pulsation period. Thus, the shock is not self similar from one cycle to the next.…”
Section: Two Shocks Per Pulsation Period?supporting
confidence: 65%
“…While 2 shocks per pulsation periods are not very rare (Fokin et al 2004 for β Cephei stars, Fokin 1992 for RR Lyrae stars), such a phenomenon has not been reported yet for classical Cepheid stars. In addition, the already detected second shock in the β Cephei star BW Vul and in RR Lyrae stars occurs normally during the stellar contraction, not during the expansion.…”
Section: Origin Of the Third Componentmentioning
confidence: 94%
“…This would help the future development of the hydrodynamical codes of pulsating stars (e.g. Fokin et al 2004), as well as of stellar interior models.…”
Section: Discussionmentioning
confidence: 99%
“…The radial-velocity variations of this star were first detected by Frost (1902). Five frequencies have been derived from a long-term spectroscopic study of β Cep, two of which were identified as a radial and non radial mode (Telting et al 1997).…”
Section: Introductionmentioning
confidence: 99%